TINJAUAN YURIDIS PENGARUH MINUMAN KERAS TERHADAP PERKELAHIAN DI LUBUKLINGGAU - Fitriyani, Fitriyani; Romadhon, Muhammad Dimas; Fuadi, Ahmad (LPPM Universitas Bina Insan, 2025)
The influence of alcohol on fights is a form of criminal act, and should be categorized as a type of criminal act that violates the law. This study aims to determine the influence of alcohol on the occurrence of fights through the application of Article 351 of the Criminal Code concerning the crime of assault. This study uses an Empirical Normative approach. Data collection techniques are carried out through interviews, observations, and document studies. The results of this study indicate that alcohol affects a person's behavior by reducing self-control, increasing aggressiveness, and worsening decision-making, which has the potential to cause physical conflict or fights. The legal efforts made by the East Lubuklinggau I Police to reduce the influence of alcohol on the occurrence of fights according to the results of the researcher's interview with Mr. AIPTU Henky Mirwadi as Head of Criminal Investigation Unit of the East Lubuklinggau I Police are by conducting patrols, legal counseling, and taking action against illegal alcohol sellers in the area of ​​the East Lubuklinggau I Police in accordance with statutory regulations.